STORM : brainstorming collaborative web environment oriented to the educational context - Galdámez, Nicolás; Sanz, Cecilia Verónica; De Giusti, Armando Eduardo (2012)
This paper details the design and development of a collaborative system that allows using the Brainstorming technique. This technique is widely used at various educational levels, and its development through computer systems adds favorable aspects both for teachers and students. STORM is a tool oriented specifically to the educational environment that allows developing Brainstorming sessions, considering the stages of idea generation, subsequent analysis of the contributions, and the connection of the various ideas in a relational map.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
International Conference on Collaboration Technologies and Systems (2012 may. 21-25 : Denver). IEEE, 2012, pp. 275-279
Keywords: EDUCACIÓN; TECNOLOGÍAS DE LA INFORMACIÓN Y DE LA COMUNICACIÓN (TICS); AMBIENTES VIRTUALES COLABORATIVOS